A Efektivitas Latihan Plyometric Depth Jump Dan Jump To Box Terhadap Keterampilan Smash Bola Voli: Kajian Pustaka: Efektivitas Latihan Plyometric Depth Jump Dan Jump To Box Terhadap Keterampilan Smash Bola Voli: Kajian Pustaka - Oktavio, Gigih Ilham; Yono, Topo; Apriliyanto, Rizki (Universitas Hamzanwadi, 2025)
The problem underlying this study is that many athletes and students still have difficulty producing hard, fast, and accurate volleyball smashes. This is due to limited leg muscle power, vertical jump height, and movement coordination. This study aims to analyze the effectiveness of two plyometric training methods, namely depth jump and jump to box, in improving volleyball smash skills. The method used was a literature review, analyzing ten relevant previous studies from 2015 to 2025. The results of the study showed that both exercises were effective in increasing leg muscle power, vertical jump height, and smash performance. Depth jumps tend to be more optimal for advanced athletes because they require high muscle reactivity, while jump to box is more suitable for beginners because it is safer and emphasizes movement control. The conclusion of this study is that although both are effective, the choice of method must be tailored to the athlete's level. A combination of both exercises is recommended to produce a more comprehensive improvement in smash skills.